Education Students' Stigma Toward Mental Health Problems: A Cross-Cultural Comparison - Gallego, José; Cangas, Adolfo J.; Aguilar, José M.; Trigueros, Rubén; Navarro, Noelia; Galván, Blanca; Smyshnov, Konstantin; Gregg, Melanie (Frontiers in Psychiatry, 2020)
One of the main obstacles to integrating individuals with severe mental disorders into society today is the stigma directed at them. Although breakthroughs in treatment have been made in recent years, many professionals continue to admit that they do not possess enough training to combat this problem. Considering this situation, the present study analyzes the existing stigma among University Education students in three countries with different education systems and cultures, namely Spain, Russia, and Canada. A total of 1,542 students from these three countries participated in the study. ANOVA, MANOVA, and Multigroup Confirmatory Factor Analysis were applied in the data analysis. The results showed that the highest rates of stigma were in Spain and the lowest were in Canada, while Russia displayed intermediate values. This work addresses the relevance of these results, the influence that cultural difference may have on education policies, and the need to implement anti-stigma programs in countries like Spain, which has a relatively high level of social stigma and where these programs are practically not applied at all.